Analisis Ekonomi Syariah Terhadap Hubungan Patron-Klien Pada Jual Beli Gabah di Kabupaten Pinrang - Jamal, Riska; Bahri S, Andi; Mahsyar, Mahsyar (Universitas Islam Negeri Alauddin Makassar, 2024)
This study aims to determine the analysis of Islamic economics on patron-client relationships in the sale and purchase of rice in Pinrang. This study is qualitative. Researchers conducted observations and interviews according to the main problem. The results of the study showed that the terms of sale and purchase had yet to be fully implemented in the transaction. The price used was based on the market price by the intermediaries. The scale deduction was reduced by 5-10 kg/sack according to the rice problem. The intermediaries imposed deferred payments. This happened because of the involvement of the patron-client relationship between farmers and intermediaries. As a result of the dependence between the two, they had a long-lasting and lasting relationship; farmers had an attitude of dependence, accepted low prices, and were easily exploited by intermediaries. Thus, the analysis of Islamic economics on the patron-client relationship in the sale and purchase of rice in Pinrang Regency is not in accordance with the provisions of Islamic economics because there is still injustice.